Molecular cloning of cDNA for double-stranded RNA adenosine deaminase, a candidate enzyme for nuclear RNA editing. - Kim, U (1994)
We have cloned human cDNA encoding double-stranded RNA adenosine deaminase (DRADA). DRADA is a ubiquitous nuclear enzyme that converts multiple adenosines to inosines in double-helical RNA substrates without apparent sequence specificity. The A --> I conversion activity of the protein encoded by the cloned cDNA was confirmed by recombinant expression in insect cells. Use of the cloned DNA as a molecular probe documented sequence conservation across mammals and detected a single transcript of 7 kb in RNA of all human tissues analyzed. The deduced primary structure of human DRADA revealed a bipartite nuclear localization signal, three repeats of a double-stranded RNA binding motif, and the presence of sequences conserved in the catalytic center of other deaminases, including a cytidine deaminase involved in the RNA editing of apolipoprotein B. These structural properties are consistent with the enzymatic signature of DRADA, and strengthen the hypothesis that DRADA carries out the RNA editing of transcripts encoding glutamate-gated ion channels in brain.